How many monic polynomials with real coefficients of degree < 1 0 0 0 have the property that f ( x 2 + x ) = ( f ( x ) ) 2 + f ( x ) for all x ?
Details and assumptions
A polynomial is monic if its leading coefficient is 1. For example, the polynomial x 3 + 3 x − 5 is monic but the polynomial − x 4 + 2 x 3 − 6 is not.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let there exist a function f(x) satisfying the conditions. Consider the function g ( x ) = f ( f ( x ) ) . Note that g ( x 2 + x ) = f ( f ( x 2 + x ) ) = f ( f ( x ) 2 + f ( x ) ) = f ( f ( x ) ) 2 + f ( f ( x ) ) = g ( x ) 2 + g ( x ) . Also note that as f(x) is monic, g(x) is also monic. Therefore, if f(x) satisfies the given conditions, so does f(f(x)).
f ( x ) = x clearly satisfies the conditions.
Note that if P ( x ) = P ( y ) whenever Q ( x ) = Q ( y ) , then there exists a polynomial R such that P ( x ) = R ( Q ( x ) ) . Therefore, the set f ( x ) , f ( f ( x ) ) , f ( f ( f ( x ) ) , . . . gives all solutions. As the degree must be less than 1000, and there exists exactly one solution for each degree that is a power of 2, our answer is ⌈ lo g 2 1 0 0 0 ⌉ = 1 1
Problem Loading...
Note Loading...
Set Loading...
Note first that for all x , ( − x − 1 ) 2 + ( − x − 1 ) = x 2 + x . So ( f ( − x − 1 ) ) 2 + f ( − x − 1 ) = f ( ( − x − 1 ) 2 + ( − x − 1 ) ) = f ( x 2 + x ) = ( f ( x ) ) 2 + f ( x ) Therefore, ( f ( x ) − f ( − x − 1 ) ) ⋅ ( f ( x ) + f ( − x − 1 ) + 1 ) = 0 The product of non-zero polynomials is non-zero, so either f ( − x − 1 ) = f ( x ) for all x or f ( x ) + f ( − x − 1 ) + 1 = 0 for all x .
In the latter case, plug in x = − 2 1 and get f ( − 2 1 ) = − 2 1 . Then plug in x = − 2 1 into the original identity for f ( x 2 + x ) to get f ( − 4 1 ) = − 4 1 . Then plug in x = − 4 1 into the same identity and get f ( − 1 6 3 ) = − 1 6 3 . . . Continuing this, we get f ( x i ) = x i for an infinite sequence x i , with x i + 1 = x i 2 + x i . It is easy to see that all x i are from − 1 to 0 and the sequence is increasing. Therefore f ( x ) = x for infintely many x , thus f ( x ) = x for all x . This polynomial obviously satisfies the conditions of the problem.
In the former case, consider polynomial g ( x ) = f ( x − 2 1 ) . The equation rewrites as g ( x ) = g ( − x ) . This implies that all coefficients of g for odd powers of x are zero, so g ( x ) = h ( x 2 ) for some polynomial h . Therefore f ( x ) = g ( x + 2 1 ) = h ( x 2 + x + 4 1 ) , so f ( x ) = p ( x 2 + x ) for some polynomial p . Rewriting the original identity in terms of p , we get p ( ( x 2 + x ) 2 + ( x 2 + x ) ) = ( p ( x 2 + x ) ) 2 + p ( x 2 + x ) So for all t that can be expressed as t = x 2 + x , we get p ( t 2 + t ) = ( p ( t ) ) 2 + p ( t ) . Since there are infinitely many such t , this identity is true for all t . So the polynomial p satisfies the same conditions (notice that it is monic as well). The degree of p is half the degree of f . This reduction cannot continue forever, and the only way it can stop is if we arrive at the polynomial f ( x ) = x . This implies that all polynomials satisfying the conditions of the problem are from the sequence f i ( x ) defined as follows: f 0 ( x ) = x ; f i + 1 ( x ) = f i ( x 2 + x ) , i = 0 , 1 , 2 , . . . Note that the degree of f i (the i -th composite power of x 2 + x ) is 2 i . Therefore the degree of f i is less than 1 0 0 0 for i = 0 , 1 , . . . , 9 , which gives 1 0 as the answer.